2012
DOI: 10.1186/2040-2392-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rare X-linked neuroligin variants by massively parallel sequencing in males with autism spectrum disorder

Abstract: BackgroundAutism spectrum disorder (ASD) is highly heritable, but the genetic risk factors for it remain largely unknown. Although structural variants with large effect sizes may explain up to 15% ASD, genome-wide association studies have failed to uncover common single nucleotide variants with large effects on phenotype. The focus within ASD genetics is now shifting to the examination of rare sequence variants of modest effect, which is most often achieved via exome selection and sequencing. This strategy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 100 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…Several mutations and CNVs in NRXN1-3 have been found to be associated with ASD with the prevalence highest for mutations in NRXN1 (Feng et al, 2006; Autism Genome Project Consortium et al, 2007; Kim et al, 2008; Yan et al, 2008; Ching et al, 2010; Pinto et al, 2010; Wisniowiecka-Kowalnik et al, 2010; Gauthier et al, 2011; Voineskos et al, 2011; Camacho-Garcia et al, 2012; Duong et al, 2012; Iossifov et al, 2012; Kong et al, 2012; Liu et al, 2012; Prasad et al, 2012; Schaaf et al, 2012; Vaags et al, 2012; Bena et al, 2013; Dabell et al, 2013; Girirajan et al, 2013; Jiang et al, 2013b; Koshimizu et al, 2013; Walker and Scherer, 2013; Cukier et al, 2014; De Rubeis et al, 2014; Egger et al, 2014; Imitola et al, 2014; Vinas-Jornet et al, 2014; Tammimies et al, 2015). Similarly, NLGN1-4 genes have been implicated in the pathogenesis of ASD with NLGN3 and 4 being the most prevalent (Jamain et al, 2003; Laumonnier et al, 2004; Ylisaukko-oja et al, 2005; Lawson-Yuen et al, 2008; Glessner et al, 2009; Yu et al, 2011, 2013; Leblond et al, 2012; O’Roak et al, 2012b; Steinberg et al, 2012; Yanagi et al, 2012; Girirajan et al, 2013; Jiang et al, 2013b; Iossifov et al, 2014; Kenny et al, 2014; Li et al, 2014a; Krumm et al, 2015; Sanders et al, 2015; Yuen et al, 2015). However, several reports also indicate the negative association of NLGN3 and 4 with autism (Vincent et al, 2004; Gauthier et al, 2005; Blasi et al, 2006; Wermter et al, 2008; Avdjieva-Tzavella et al, 2012; Liu et al, 2013b; Xu et al, 2014).…”
Section: Trans-synaptic Adhesion Molecules Play Important Roles In Thmentioning
confidence: 99%
“…Several mutations and CNVs in NRXN1-3 have been found to be associated with ASD with the prevalence highest for mutations in NRXN1 (Feng et al, 2006; Autism Genome Project Consortium et al, 2007; Kim et al, 2008; Yan et al, 2008; Ching et al, 2010; Pinto et al, 2010; Wisniowiecka-Kowalnik et al, 2010; Gauthier et al, 2011; Voineskos et al, 2011; Camacho-Garcia et al, 2012; Duong et al, 2012; Iossifov et al, 2012; Kong et al, 2012; Liu et al, 2012; Prasad et al, 2012; Schaaf et al, 2012; Vaags et al, 2012; Bena et al, 2013; Dabell et al, 2013; Girirajan et al, 2013; Jiang et al, 2013b; Koshimizu et al, 2013; Walker and Scherer, 2013; Cukier et al, 2014; De Rubeis et al, 2014; Egger et al, 2014; Imitola et al, 2014; Vinas-Jornet et al, 2014; Tammimies et al, 2015). Similarly, NLGN1-4 genes have been implicated in the pathogenesis of ASD with NLGN3 and 4 being the most prevalent (Jamain et al, 2003; Laumonnier et al, 2004; Ylisaukko-oja et al, 2005; Lawson-Yuen et al, 2008; Glessner et al, 2009; Yu et al, 2011, 2013; Leblond et al, 2012; O’Roak et al, 2012b; Steinberg et al, 2012; Yanagi et al, 2012; Girirajan et al, 2013; Jiang et al, 2013b; Iossifov et al, 2014; Kenny et al, 2014; Li et al, 2014a; Krumm et al, 2015; Sanders et al, 2015; Yuen et al, 2015). However, several reports also indicate the negative association of NLGN3 and 4 with autism (Vincent et al, 2004; Gauthier et al, 2005; Blasi et al, 2006; Wermter et al, 2008; Avdjieva-Tzavella et al, 2012; Liu et al, 2013b; Xu et al, 2014).…”
Section: Trans-synaptic Adhesion Molecules Play Important Roles In Thmentioning
confidence: 99%
“…Considering that males have higher predisposition in ASD etiology, an involvement of the X-chromosome in autism susceptibility has been suggested by genetic and cytogenetic studies [9,10,11,12,13] and several putative candidate genes, including neuroligins, have been largely investigated [7,8,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Nonetheless, taking advantages of the new sequencing technologies, further insights might be provided in discovering new X-linked genetic variants associated with ASD predisposition or its etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of exons 4, 5, and 6 in NLGN4X have been also found in autistic children, suggesting that alternative splicing variants might lead to abnormal neuroligin function in ASD [29,30]. Moreover, several noncoding genetic variants have been specifically found in ASD patients [31,32,33,34,35,36,37]. All these variations often segregate into ASD families [12,13] and can also be associated with different cognitive phenotypes, such as intellectual and language disabilities [32,37], highlighting the role of neuroligins in the ASD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the genes encoding the presynaptic cell-adhesion molecules, neurexins, and their postsynaptic binding partners, neuroligins, have been implicated in non-syndromic ASDs (Gauthier et al, 2011; Camacho-Garcia et al, 2013; Vaags et al, 2012; Steinberg et al, 2012; Jamain et al, 2003; Feng et al, 2006). Additionally, mutations in genes coding for other members of the neurexin superfamily, contactin associated protein-2 ( CNTNAP2 ; Alarcón et al, 2008; Arking et al, 2008) and contactin associated protein-4 ( CNTNAP4 ; Karayannis et al, 2014), have been identified in cases of ASD.…”
Section: Overview Of Monogenic Mouse Models Of Asdsmentioning
confidence: 99%